Morphological, spectral and toxicological features of new composite material of titanium nanodioxide with nanosilver for use in medicine and biology - M.M. Zahornyi; O.P. Yavorovsky; V.M. Riabovol; N.I. Tyschenko; T.F. Lobunets; T.V. Tomila; O.V. Shirokov; A.V. Ragulya; Ye.M. Anisimov (Medičnì Perspektivi)
The results of this study indicate that titanium dioxide nanoparticles (nano-TiO2) possess adsorptive, photocatalytic, bactericidal, virucidal and fungicidal properties, which are used in antibacterial coating, for air and water disinfection. In parallel with studies of the physicochemical characteristics of titanium dioxide, its toxicological assessment was carried out to prevent possible harmful effects on humans and the biosphere objects, followed by an assessment of the nano-TiO2 hazard class. To enhance these useful properties of nano-TiO2, nanopowders of titanium dioxide and a composite of titanium dioxide were synthesized with a silver (nano-TiO2 /Ag) by way of chemical precipitation of metatitanic acid adding silver nitrate to the composite at 500-600°C.  It was stated that the synthesized nanostructures have the following characteristics: anatase crystal structure of TiO2 (anatase, rutile, brookite – natural crystalline modifications of TiO2), the size of Ag nanoparticles is 35-40 nm, TiO2 – 13-20 nm. Nanocomposite has surface defects of the crystal lattice (oxygen vacancies, impurities, excess electrons or holes), silver nanoparticles are localized on the surface of anatase TiO2, which increases adsorptive, photocatalytic, biological and specifically antibacterial properties of the composite material nano-TiO2/Ag. According to the parameters of acute intraperitoneal toxicity, the studied nanocomposite anatase nano-TiO2/Ag was classified as a moderately dangerous substance (material). Nano-TiO2 and TiO2/Ag nanocomposites do not cause local irritation to the skin, yet have a mildly irritating effect on the mucous membrane of the eye, and are also characterized by a weak sensitization effect.